Study of Antibiotic Resistance of the Oropharyngeal Hemolytic Microflora in Preschool Children - Kolesnikova, S G; Kolesnikova, Yu V; Solovyova, A G; Styrov, S V; Moiseeva, I Y; Kuleshov, I N (KnE Energy, 2018)
It is impossible to imagine modern medical practice without antibiotic therapy. However, the rapid development of the pharmaceutical industry expands free access of the population to antibacterial drugs. At the same time, the illiteracy of people with respect to the principles of rational antibiotic therapy also increases. The problem of microbial resistance to antibacterial drugs remains relevant to this day. Special attention should be paid to rational antibiotic therapy applied to children.The purpose of this work was to study the resistance of hemolytic microorganisms, which are often the cause of upper respiratory infection in preschool children, to the main antibacterial drugs used in pediatric practice. The results of this scientific research can be advisory and useful to pediatricians and other specialists whose professional activities are related to children’s health. Keywords: hemolytic active microorganisms, bacterial carriage, antibiotic resistance, children’s health